The PAICE project: Integrating health and health equity into UK climate change policy [version 2; peer review: 1 approved, 2 approved with reservations] - Charles Simpson; Gemma Moore; David Osrin; James Milner; Phil Symonds; Rosemary Green; Simon Vakeva-Baird; Ruth Unstead-Joss; Irene Pluchinotta; Catalina Turcu; Nici Zimmermann; Ke Zhou; et al. (Wellcome Open Research)
This paper announces a new initiative - the research project Policy and Implementation for Climate & Health Equity (PAICE), which aims to investigate the complex systemic connections between climate change action, health and health equity, for translation of evidence into policy and practice in the UK. Using transdisciplinary approaches, PAICE will: (1) co-develop a programme theory and linked monitoring and evaluation plan, (2) work with the UK Climate Change Committee (CCC) and the Greater London Authority (GLA) using system dynamics to analyse national and local policy opportunities, (3) build an integrated model of the effects of these policies on population health, health equity and greenhouse gas emissions, (4) apply the findings to the CCC monitoring framework and GLA policy development, and (5) use the programme theory to help evaluate achievement of PAICE processes and objectives. If successful, PAICE will have helped to establish a systems capability to (i) monitor whether Government plans are on track to deliver their climate targets and associated health impacts and (ii) understand how relevant policy and implementation approaches could be enhanced.